A New Stability-Indicating RP-HPLC Method for the Simultaneous Estimation of Remogliflozin and Teneligliptin in Bulk and Pharmaceutical Dosage Form - Kumar, Badupula Sravan; Redamala, Roopa (International Journal of Pharmaceutical Investigation, 2026)
Aim To estimate Remogliflozin and Teneligliptin simultaneously in bulk and pharmaceutical dosage forms, including forced degradation studies, a simple, Robust, and Stability-Indicating (RP-H-P-L-C) method has been developed and validated. Materials and Methods Discovery (150 mm × 4.6 mm 5 µm) C18 is used as the phase which is stationary for separation, and 0.01N Dibasic Sodium Phosphate Buffer (Na2HPO4) at pH 4.6 and acetonitrile in a 65:35 ratio make up the mobile phase. A maximum wavelength of 210 nm, a rate of flow of 1.0 mL/min, and a temp of 30ºC were all maintained. Results Teneligliptin and Remogliflozin were shown to have average retention durations of 2.282 and 2.684 min, respectively. Teneligliptin and Remogliflozin were found to have Relative Standard Deviations (R-S-D) of 0.8 and 0.7, respectively. Teneligliptin and Remogliflozin both had recovery rates of 99.77% and 99.91%, respectively. Teneligliptin and Remogliflozin's regression equations yielded L.O.D and L.O.Q values of 0.04, 0.13, and 0.30, 0.89, respectively. Remogliflozin's regression equation is y=31865x+22823, but Teneligliptin's is y=40034x + 2044.4. Because the RTs were shortened, the run time was also shortened. This suggests that the created approach is simple and economical, which makes it appropriate for regular quality control testing in industries. Conclusion Because the RTs were shortened, the run time was also shortened. This suggests that the created approach is simple and economical, which makes it appropriate for regular quality control testing in industries.
Keywords: Chromatogram; Remogliflozin; RP-H-P-L-C; Standard Deviation; Teneligliptin